2010
DOI: 10.3758/app.72.4.1079
|View full text |Cite
|
Sign up to set email alerts
|

The prioritization of perceptual processing in categorization

Abstract: The influence of attention on perception has been the focus of much research in the last 30 years. Typically, the effects of visual attention have been examined using tasks in which attention is directed by a cue to a particular location and a judgment is required about a stimulus at this location. These paradigms have demonstrated that spatially cued attention enhances stimulus discrimination (Downing, 1988;Hawkins et al., 1990;Henderson, 1996;Lu & Dosher, 1998;Luck, Hillyard, Mouloua, & Hawkins, 1996;Posner,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 73 publications
(138 reference statements)
0
13
1
Order By: Relevance
“…Moreover, the most parsimonious explanation of the data is that a similar comparison process underlies both tasks. Indeed, one of the important aspects of the exemplar models of absolute identification is that they have also provided a very good account of data from other tasks including categorisation (Nosofsky, 1986;Lamberts, 2000, Guest & Lamberts, 2010, recognition (Brockdorff & Lamberts, 2000;Zaki & Nosofsky, 2001), same-different judgements (Cohen & Nosofsky, 2000), and visual search (Guest & Lamberts, 2011). This suggests that these processes are fundamental to cognition, adding weight to the notion that the similarity of the pattern of responses in absolute identification and simultaneous matching is an indication of a common underlying process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the most parsimonious explanation of the data is that a similar comparison process underlies both tasks. Indeed, one of the important aspects of the exemplar models of absolute identification is that they have also provided a very good account of data from other tasks including categorisation (Nosofsky, 1986;Lamberts, 2000, Guest & Lamberts, 2010, recognition (Brockdorff & Lamberts, 2000;Zaki & Nosofsky, 2001), same-different judgements (Cohen & Nosofsky, 2000), and visual search (Guest & Lamberts, 2011). This suggests that these processes are fundamental to cognition, adding weight to the notion that the similarity of the pattern of responses in absolute identification and simultaneous matching is an indication of a common underlying process.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the TAF methodology is that it enables a purer estimate of processing speed than standard accuracy or RT designs, because the estimate is not contaminated by performance levels or the time taken to start processing. Indeed, this approach has been used to model the time course of performance and gain estimates of visual information processing rates in a variety of tasks such as perceptual categorization, visual search, recognition, and word identification (Brockdorff & Lamberts, 2000;Carrasco & McElree, 2001;Guest & Lamberts, 2010, 2011Kent, Howard, & Gilchrist, 2012; see Kent, Guest, Adelman, and Lamberts, 2014, for a review).…”
Section: Estimating Processing Speed By Modeling the Dynamics Of Perfmentioning
confidence: 99%
“… Lamberts (1995 , 1998) suggested that processing rates were independent of the utility of the dimension (how important a dimension is for correct categorization) and in several experiments demonstrated that perceptual processing rates were determined largely by perceptual salience of the dimension and not dimension utility (changing the category structure had little effect on processing rates; see also Ashby and Maddox, 1994 ; Maddox and Bogdanov, 2000 ; Maddox, 2001 ; Maddox and Dodd, 2003 ). However, given that visual attention is known to modulate sensory processing (e.g., Luck et al, 1994 ; Treue, 2001 ; Carrasco et al, 2002 ), accelerate the rate of perceptual processing ( Carrasco and McElree, 2001 ), and can be flexibly allocated ( Bundesen, 1990 ), Guest and Lamberts (2010) re-examined conditions under which knowledge of the category structure can influence perceptual processing rates. Their experiments used a categorization task in which all stimulus dimensions needed to be processed in order to ensure correct categorization but where stimulus dimensions clearly differed in their diagnosticity (how diagnostic they were of category membership) and diagnosticity was pitted against the perceptual salience of stimulus dimensions.…”
Section: Identification and Categorizationmentioning
confidence: 99%